(untitled) (Cadernos ESP, 2021)
To describe the experience of a research department at the School of Public Health of Ceará in disclosing preliminary data from the clinical study using the Elmo helmet as a hospital support strategy in the fight against Covid-19 to society. Experience report, described in August 2021, by researchers from the Scientific Investigation Center of the School of Public Health of Ceará. The event took place on November 4th with the release of research data. There was the participation of 1,400 people and 4,500 Views, being broadcast on the youtube channel of the Escola de Saúde Pública. The speakers were the main creators of the technology. The dissemination of research data to society is necessary, being an initiative to improve processes and develop capabilities for the results of research carried out in the institution.